(untitled) (Jurnal Manajemen dan Kewirausahaan, 2007)
This research attempts to investigate the effect of downward sloping demand curves for stock on firms’ financing decisions. For the same size of equity issuance, firms with steeper slope of demand curves for their stocks experience a larger price drop in their share price compare to their counterparts. As a consequence, firms with a steeper slope of demand curves are less likely to issue equity and hence they have higher leverage ratios. This research finds that the steeper the slope of demand curve for firm’s stock, the higher the actual leverage of the firm. Furthermore, firms with a steeper slope of demand curves have higher target leverage ratios, signifying that these firms prefer debt to equity financing in order to avoid the adverse price impact of equity issuance on their share price.